(untitled) (Journal of Applied Oral Science, 2021)
Objective: To evaluate the surface morphology and in vitro leachability of temporary soft linings modified by the incorporation of antifungals in minimum inhibitory concentrations (MIC) for Candida albicans biofilm. Methodology: Specimens of soft lining materials Softone and Trusoft were made without (control) or with the addition of nystatin (Ny), miconazole (Mc), ketoconazole (Ke), chlorhexidine diacetate (Chx), or itraconazole (It) at their MIC for C. albicans biofilm. The surface analyses were performed using Confocal laser scanning microscopy after 24 h, 7 days, or 14 days of immersion in distilled water at 37ºC. In vitro leachability of Chx or Ny from the modified materials was also measured using Ultraviolet visible spectroscopy for up to 14 days of immersion in distilled water at 37ºC. Data (μg/mL) were submitted to ANOVA 1-factor/Bonferroni (α=0.05). Results: Softone had a more irregular surface than Trusoft. Morphological changes were noted in both materials with increasing immersion time, particularly, in those containing drugs. Groups containing Chx and It presented extremely porous and irregular surfaces. Both materials had biexponential release kinetics. Softone leached a higher concentration of the antifungals than Trusoft (p=0.004), and chlorhexidine was released at a higher concentration than nystatin (p<0.001). Conclusions: The surface of the soft lining materials changed more significantly with the addition of Chx or It. Softone released a higher concentration of drugs than Trusoft did, guiding the future treatment of denture stomatitis.